1991
DOI: 10.1002/ajim.4700190404
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive hazards of fire fighting II. Chemical hazards

Abstract: Studies of the health of fire fighters have historically focused on non-malignant respiratory disease and cancer. More recently, concerns have surfaced about reproductive health effects in many areas of the workforce, including fire fighting. These concerns prompted this review of chemical exposures that may contribute to adverse reproductive health outcomes in male as well as female fire fighters. A review of the industrial hygiene literature was undertaken to identify agents commonly found in fire smoke. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 146 publications
0
22
0
Order By: Relevance
“…Research conducted in the 1980’s suggested that toxic exposures experienced by male firefighters may increase the likelihood of birth defects among their offspring [10]. Similarly, preliminary data from the same period indicated that the exposure to carbon monoxide and high ambient temperatures may increase the risk of birth defects among pregnant female firefighters and highlight the reproductive dangers of firefighting [11,12]. Evidence also suggests that pregnant women’s exposure to loud noises (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the 1980’s suggested that toxic exposures experienced by male firefighters may increase the likelihood of birth defects among their offspring [10]. Similarly, preliminary data from the same period indicated that the exposure to carbon monoxide and high ambient temperatures may increase the risk of birth defects among pregnant female firefighters and highlight the reproductive dangers of firefighting [11,12]. Evidence also suggests that pregnant women’s exposure to loud noises (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recognized or probable carcinogens to which fire fighters can be exposed include asbestos, benzene, diesel engine exhaust, ethylene oxide, polychlorinated biphenyls, polycyclic aromatic hydrocarbons, among others [International Agency for Research on Cancer (IARC), Aronson et ai. Jankovic et al, 1991;McDiarmid et al, 1991;Siemiatycki, 19911. Studies of fire fighters have reported excesses of brain cancer, malignant melanoma, leukemia, colon cancer, and other various cancers [Howe and Burch, 1990;Sama et al, 1990;Demers et al, 1992;Guidotti, 19931. Substances which may potentiate a cardiovascular reaction in fire fighters include carbon monoxide and dioxide, acrolein, benzene, cyanide, hydrogen chloride, particulates, sulphur oxides, and organic solvents [Kristensen, 1989a1.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION Fire®ghters are exposed under uncontrolled conditions to a wide variety of toxic chemicals including known and suspected carcinogens, such as benzene and formaldehyde in wood smoke, polycylic aromatic hydrocarbons (PAHs) in soots and tars, arsenic in wood preservatives, asbestos in building insulation, diesel engine exhaust, and dioxins [Froines et al, 1987;IARC 1987;Jankovic et al, 1991;McDiarmid et al, 1991;Siemiyatcki, 1991]. The widespread introduction of synthetic building materials in the late 1950s increased the complexity of the ®re®ghters' exposure.…”
mentioning
confidence: 99%